Hospital Volunteering Experiences Suggest that New Policies are Needed to Promote their Integration in Daily Care: Findings from a Qualitative Study - Gonella, Silvia (Zdr Varst, 2019)
OBJECTIVE: To explore Hospital Volunteers’ (HVs) motivations and experiences, as well as the strategies they adopt to overcome challenging situations during volunteering and the needs they perceive. METHODS: Eleven Italian HVs were purposively approached between January and July 2016, using face-to-face semi-structured interviews. The interviews were audio-recorded, transcribed verbatim and analysed using the descriptive phenomenological approach. RESULTS: Hospital volunteering emerged as a complex experience characterised by five themes: (a) becoming a volunteer; (b) developing skills; (c) experiencing conflicting emotions; (d) overcoming role difficulties by enacting different resources and strategies; and (e) addressing emerging needs. CONCLUSIONS: According to the findings, hospital policies aimed at promoting volunteer integration in daily care are needed and should be based on (a) a shared vision between the hospital and the volunteer associations regarding the HVs’ role and skills; (b) the development of integrated models of care combining different workforces (i.e. professionals and volunteer staff); (c) appropriate training of HVs at baseline; (d) individualised continuous education pathways aimed at supporting HVs both emotionally and in the development of the required skills; and (e) tailored education that is directed to health-care staff aimed at helping them to value the service provided by HVs.